Oxidation‐etching induced morphology regulation of Cu catalysts for high‐performance electrochemical N2 reduction. Issue 2 (29th April 2020) - Ji, Xuqiang; Wang, Ting; Liu, Qian; Luo, Yongsong; Lu, Siyu; Chen, Guang; Gao, Shuyan; Asiri, Abdullah M.; Sun, Xuping
Abstract: Renewable‐electricity‐driven N2 reduction is an attractive approach for ambient NH3 synthesis, but active electrocatalysts are needed to enable the N2 reduction reaction. Monolithic electrodes with active components anchored on conductive supports provide many advantages like structural stability, large surface area, and low electrical resistance. Here, a novel "oxidation‐etching" strategy is proposed to carve the surface of Cu foam into structures of particles, cubes, and sheets for N2 reduction electrocatalysis. The optimal catalyst achieves a Faradic efficiency as high as 18% at −0.35 V vs reversible hydrogen electrode (RHE) and a large NH3 yield of 2.45 × 10 −10 mol s −1 cm −1 at −0.40 V vs RHE in 0.1 M HCl. Notably, it also shows superior long‐term electrochemical durability, with the preservation of electro‐activity for at least 20 hours. Abstract : An "oxidation‐etching" strategy is proposed to carve the surface of Cu foam into structures of particles, cubes, and sheets for N2 reduction electrocatalysis. In 0.1 M HCl, the Cu nanoparticle catalyst achieves a Faradic efficiency as high as 18% at −0.35 V vs RHE and a large NH3 yield of 2.45 × 10 −10 mol s −1 cm −1 at −0.40 V vs RHE.